Pengaruh Pelatihan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada CV. Surya Kencana Food Jombang - Mardi Astutik (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
Job training and discipline is closely related to employee performance improvement in an organization. The better the job training and work discipline, the greater the encouragement of employees to move forward together with the organization. The aim of this study was to examine and explain directly influence job training and work discipline on employee performance. The research method uses quantitative research. Measurement scale used is the Likert scale, the population in this study all the production employees CV. Surya Kencana Food Jombang amounted to 280 people, a large sample used as many as 74 people. Penguumpulan engineering data using observations, questionnaires, interviews and documentation. Variables that are rigorous job training and work discipline on employee performance. Data analysis using multiple linear regression analysis with significance level α = 0.05. The results showed that the job training (X1) has a test statistic t count equal to 2.148 and 0.026 significance, since the value t sig = 0.026 < α = 0.05, thus it can be stated that the job training influence on employee performance. Labour discipline (X2) has a test statistic t count equal to 2.243 and significant amounted to 0.040 since the value t sig = 0.040 < α = 0.05, thus it can be stated that the disciplinary effect on the work performance of employees. These results indicate that job training and work discipline and significant positive effect on employee performance in CV. Surya Kencana Food Jombang